Faktor-faktor Penghambat Pengelolaan Usaha SD3 Digital Printing Desa Yosonegoro Kecamatan Limboto Barat Kabupaten Gorontalo - Nurain Gawa; Ellys Rachman; Sabriana Octaviana Gintulangi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This research aims to identify and analyze factors that hinder the management of the SD3 Digital Printing business located in Yosonegoro Village, West Limboto District, Gorontalo Regency. This research uses a qualitative approach with descriptive methods. Data was obtained through interviews, direct observation and documentation. The research results show that there are three factors that become obstacles in business management, namely limited raw materials which cause production delays, a lack of facilities and infrastructure such as printing equipment and limited production space, and a lack of human resources both in terms of numbers and technical skills. These obstacles have an impact on reducing production efficiency and customer satisfaction. Therefore, it is recommended that improvements be made in supply chain management, investment in production facilities, and training for workers to improve competency and business performance.